Study of Low Temperature-Treated Aldolized Cellulose Nanocrystals for Enhancing Dye Separation and Self-Healing Properties of Graphene Oxide Membranes - He, Yiling (Langmuir : the ACS journal of surfaces and colloids, 2024)
Graphene oxide (GO) membranes with a 2D layered structure and nanoscale channels have great application prospects for dye wastewater purification. In this paper, ethylenediamine (EDA) was grafted onto the surface of GO nanosheets at 70 °C and aldolized cellulose nanocrystals (ICNC) were introduced to form EDA-ICNC hydrogel structures between the GO nanosheets by Schiff base reaction. The interlayer structure of the membrane was determined by adjusting the amount of ICNC added and the degree of aldolization, and the EGOICNC-24 membrane with the best performance was prepared. The water flux is not only 12 times higher than that of GO membrane but also has a good separation ability for dye molecules with a molecular weight around 300. Following the EDA-ICNC-24 hydrogel cross-linking process, the tensile strength of the EGOICNC-24 membrane exhibited a 173% increase relative to that of the GO membrane. Additionally, the dye rejection rate reached 97.16% after 130 h of dye separation. When the surface of the membrane was damaged, it was self-healed by regulating the repair temperature and adding a very small amount of ICNC to undergo a dynamic Schiff base reaction and a synergistic effect of hydrogen bonding